Internal and External Locus of Control of Engineering Workforce in a Power Distribution Utility: Implications for Job Performance - Modise, Disebo; Rambe, Patient (African Journal of Business and Economic Research (AJBER), 2017)
In view of the high risk, high voltage environments which the Eskom Bloemfontein engineering workforce (engineers, technologists, and technicians) is exposed to in the design, installation and maintenance of coal-fired power plants, sub-stations, transmission lines and electrical equipment, their psychological dispositions especially locus of control (LOC) should be an interesting area of research interest. The influence of LOC of the engineering workforce on improved job performance is critical to eliminating power related risks, accidents and deaths emanating from work-related fatigue, job stress and exhaustion. This study adopts a revised Rotter’s LOC Scale questionnaire to explore the combined influence of internal and external locus of control on organisational performance. The results demonstrate a positive relationship between internal locus of control and job performance. It also demonstrates that a sizable number of the Eskom engineering workforce are easily influenced by external forces, with implications for the job performance of the engineering workforce.
Published Article
Keywords: Locus of control; Job performance; Engineering workforce; ESKOM